Behaviour adoption approaches during public health emergencies: implications for the COVID-19 pandemic and beyond. Issue 1 (29th January 2021) - Jalloh, Mohamed F; Nur, Aasli A; Nur, Sophia A; Winters, Maike; Bedson, Jamie; Pedi, Danielle; Prybylski, Dimitri; Namageyo-Funa, Apophia; Hageman, Kathy M; Baker, Brian J; Jalloh, Mohammad B; Eng, Eugenia; et al.
Abstract : Human behaviour will continue to play an important role as the world grapples with public health threats. In this paper, we draw from the emerging evidence on behaviour adoption during diverse public health emergencies to develop a framework that contextualises behaviour adoption vis-à-vis a combination of top-down, intermediary and bottom-up approaches. Using the COVID-19 pandemic as a case study, we operationalise the contextual framework to demonstrate how these three approaches differ in terms of their implementation, underlying drivers of action, enforcement, reach and uptake. We illustrate how blended strategies that include all three approaches can help accelerate and sustain protective behaviours that will remain important even when safe and effective vaccines become more widely available. As the world grapples with the COVID-19 pandemic and prepares to respond to (re)emerging public health threats, our contextual framework can inform the design, implementation, tracking and evaluation of comprehensive public health and social measures during health emergencies.